2022
DOI: 10.3389/fimmu.2022.947983
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 family cytokines in chronic rhinosinusitis with nasal polyps: From experiments to the clinic

Abstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is considered a nasal sinus inflammatory disease that can be dominated by immune cells and cytokines. IL-10 family cytokines exert essential functions in immune responses during infection and inflammation. Recently, the understanding of the roles of the IL-10 family in CRSwNP is being reconsidered. IL-10 family members are now considered complex cytokines that are capable of affecting epithelial function and involved in allergies and infections. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 93 publications
0
9
0
1
Order By: Relevance
“…IL-10R is the receptor of IL-10. IL-10, a typical Th2 cytokine, is capable of regulating M2 macrophages polarization and plays an essential role in regulating inflammatory responses of CRSwNP ( 46 ). However, a recent study indicated that the IL-10 production ability of M2 macrophages was impaired in ECRSwNP, though the number of M2 macrophages was increased ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-10R is the receptor of IL-10. IL-10, a typical Th2 cytokine, is capable of regulating M2 macrophages polarization and plays an essential role in regulating inflammatory responses of CRSwNP ( 46 ). However, a recent study indicated that the IL-10 production ability of M2 macrophages was impaired in ECRSwNP, though the number of M2 macrophages was increased ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL‐10 level was lower in patients with CRSwNP and CRSsNP than that in healthy controls, 99 while another study showed no significant difference in IL‐10 level in nasal mucosal tissue between CRSwNP and control subjects 100 . Since these studies involved the patients from different regions, Xuan et al 101 . attributed the difference in these findings to immunologic heterogeneity of CRS patients in different regions.…”
Section: Characteristics Of Mucin Hypersecretion In Different Endotyp...mentioning
confidence: 99%
“…97,98 IL-10 level was lower in patients with CRSwNP and CRSsNP than that in healthy controls, 99 while another study showed no significant difference in IL-10 level in nasal mucosal tissue between CRSwNP and control subjects. 100 Since these studies involved the patients from different regions, Xuan et al 101 attributed the difference in these findings to immunologic heterogeneity of CRS patients in different regions. IL-10 prevents protein misfolding via STAT1 and STAT3 signal transduction pathways, and thereby maintains mucin production in goblet cells and integrity of the mucus barrier (Figure 2).…”
Section: Il-10 and Mucinmentioning
confidence: 99%
“…M2a macrophage also releases IL‐10, CCL22, and CCL17, which promote the infiltration of Th2 cells. The combination of IL‐10 and IL‐4 enhances the expression of M2a‐related genes in bone marrow‐derived macrophages, and increases eosinophil migration [81]. Additionally, IL‐13 stimulates the expression of low‐affinity IgE receptors CD23, MHC‐II, and phagocytic mannose receptors in monocytes of patients with asthma, thereby facilitating inflammatory responses [82].…”
Section: Il‐4/il‐13 Pathway In Nasal Type 2 Inflammationmentioning
confidence: 99%